2003
DOI: 10.1002/chem.200204508
|View full text |Cite
|
Sign up to set email alerts
|

On the Electronic Structures of the 1,3‐Diboracyclobutane‐1,3‐diyls and Their Valence Isomers with a B2E2 Skeleton (E=N, P, As)

Abstract: The concept of through-space versus through-bond interactions on the stabilization of biradical structures with a singlet or triplet ground state is evaluated for the 1,3-diboracyclobutane-1,3-diyls and related congeners. Singlet biradicals are favored when the intermediate units E feature singlet character (PH(2) (+), AsH(2) (+)), while E fragments with triplet character (NH(2) (+)) induce small energy separations between the lowest singlet and triplet states. These considerations are supported by quantum che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…Oppositely, the optimized geometries of compounds 1 and 2 in their lowest triplet excited states bear anti-pyramidalization of the two N atoms, leading to a loss of planarity of the fourmembered ring. The DE S-T values for compounds 1 and 2 are similar to other reported B 2 E 2 (E = N, P, As) four-ring compounds, [24] but smaller than in N 2 S 2 . Hence, the population of the antibonding p* LUMO orbital leads to a loss of aromaticity and a concomitant increase in the biradicaloid character.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Oppositely, the optimized geometries of compounds 1 and 2 in their lowest triplet excited states bear anti-pyramidalization of the two N atoms, leading to a loss of planarity of the fourmembered ring. The DE S-T values for compounds 1 and 2 are similar to other reported B 2 E 2 (E = N, P, As) four-ring compounds, [24] but smaller than in N 2 S 2 . Hence, the population of the antibonding p* LUMO orbital leads to a loss of aromaticity and a concomitant increase in the biradicaloid character.…”
Section: Resultssupporting
confidence: 87%
“…The adiabatic DE S-T values are similar at both levels of theory, but they are relatively large for yielding pure biradicaloid species. The DE S-T values for compounds 1 and 2 are similar to other reported B 2 E 2 (E = N, P, As) four-ring compounds, [24] but smaller than in N 2 S 2 .…”
Section: Resultssupporting
confidence: 87%
“…Indeed, calculations predict the BNBN diradical to be some 350 kJ mol À1 higher in energy than its butadiene isomer. 42 The synthesis of 11 P , 14 P , and 19 P suggests that the unique electronic properties of heavier main group elements will allow for the preparation of a variety of new structural moieties that are difficult or impossible to access in the corresponding carbon and nitrogen series. …”
Section: Resultsmentioning
confidence: 99%
“…Our own calculations, 40,42 carried out on the parent compound XIX P (H atoms at phosphorus and boron centers) showed that the singlet state is lower in energy than the triplet state by 17.2 kcal/mol, suggesting an interaction between the two radical sites. The nature of the coupling of the two radical sites (positive p-orbital overlap) was apparent from the highest occupied molecular orbital (HOMO) (Fig.…”
mentioning
confidence: 92%
“…The 2,2-electron-withdrawing-group-substituted singlet 1,3-diradicals are categorized as Type-1 diradicals [1,27], which possess a π-single-bonding character (–π–, closed-shell character) between the two radical sites. The role of the alkoxy group (OR) on the lifetime ( k = 1/τ) was investigated by combined studies of experiments and quantum chemical calculations [26,28].…”
Section: Introductionmentioning
confidence: 99%